Small RNA deep sequencing‐based detection and further evidence of DNA viruses infecting sweetpotato plants in Tanzania. (31st May 2014) - Mbanzibwa, D.R.; Tugume, A.K.; Chiunga, E.; Mark, D.; Tairo, F.D.
Abstract Small interfering RNA deep sequencing (SRDS) was used to detect viruses in 23 sweetpotato plants, collected from various locations in Tanzania. Alignment of small RNA reads using a MAQ program recovered genomes of viruses from five families, namely Geminiviridae (2), Closteroviridae (1), Betaflexiviridae (1), Caulimoviridae (1) and Potyviridae (1). This was in agreement with the variation of symptoms observed on sweetpotato plants in fields and screen house, which included leaf curl, vein yellowing, chlorosis, stunted growth and brown blotches. PCR was also used to confirm the occurrence of viruses associated with leaf curl and symptomless infections. A complete genome (2768 nucleotides) was obtained for a sweepovirus that was 89.9% identical to the strain of Sweet potato leaf curl Sao Paulo virus (SPLCSPV; Begomovirus) reported in South Africa. Sweepoviruses are known to undergo frequent recombinations and evidence for this was found in the SPLCSPV sequence studied. The SRDS‐based results indicated occurrence of the poorly studied Sweet potato badnavirus B (SPBV‐B) and Sweet potato badnavirus A (collectively known as Sweet potato pakakuy virus; SPPV; Caulimoviridae) in sweetpotato plants in Tanzania. A 5′‐end partial sequence (3065 nucleotides), encoding hypothetical, movement and coat proteins, was obtained and found to be 86.3% and 73.1% identical to SPBV‐B and SPBV‐A, respectively. A survey for the distribution of SPPV and Sweet potato symptomless mastrevirus 1 (SPSMV‐1) showed that these viruses were wide spread and co‐infecting sweetpotato plants in Tanzania. The importance of East Africa as a hot spot for the diversity and evolution of sweet potato viruses is discussed.